Exploring risk factors of drive for muscularity and muscle dysmorphia in male adolescents from a resource-limited setting in Burkina Faso - Terhoeven, Valentin; Nikendei, Christoph; Bountogo, Mamadou; Friederich, Hans-Christoph; Ouermi, Lucienne; Sié, Ali; Harling, Guy; Bärnighausen, Till (Scientific reports, 2023)
In low-income countries, Muscle Dysmorphia (MD) has only been investigated in adult south African amateur-bodybuilders. To date, there is no epidemic study about MD or its cardinal symptom “drive for muscularity” (DFM) and its impact on young men’s lives in African low-income settings. We analyzed a population-representative cross-sectional study of 838 adolescent males aged 12-20 in the rural northwestern Burkina Faso. Participants were assessed for MD with the research criteria of Pope and its cardinal symptom DFM based on the DFM scale (DMS). Since DFM has not been studied in a comparable sample so far, all possible influencing variables were examined exploratively in a linear regression model. Many respondents were underweight (41.5%) and few overweight (1.3%). No-one met standard clinical MD criteria. While 60.1% of 837 wished to be more muscular, only 8.7% of 824 desired a lower body-fat percentage. Regression analysis revealed that higher DMS scores were associated with greater internalization of the muscular body ideal, going to school, living in a rural area, older age, and a history of having faced sexual harassment or assault, but not with media exposure. Our results show that levels of DMS in Burkinabe adolescents were elevated. Risk factors for DFM in environmental circumstances where undernutrition and poverty are common are discussed.
Gesehen am 06.05.2024